Understanding gender and corruption : Domains and Challenges - Kihl, Lisa A.; Williams, Sope; Krambia-Kapardis, Maria (My University, 2025)
The chapters in this handbook underscore the immense challenge scholars, practitioners, government officials, and legal institutions face in understanding the gendered nature of corruption: how it happens, who is able to abuse authority for personal gain, and the impact of corruption on individuals, organizations, and society. The evidence presented makes clear that local and global anti-corruption strategies need to address these issues through a gendered lens to ensure women’s experiences are represented in policy design.